Биологические эффекты нейтронов разных энергий - Жербин Е. А. Евгений Александрович; Капчигашев С. П. Сидор Павлович; Коноплянников А. Г. Анатолий Георгиевич; Лучник Н. В. (Москва, Энергоатомиздат, 1984)
Авт. указаны на обороте тит. л.